The Impact of Computer Technology on Learning Listening and Speaking in the Language Classroom - Rasulova Zukhra Bakhramovna; Karayeva Dinara Khaydar qizi (Zien Journals, 2022)
In the article about the progress of studying the spread of information and network technologies in the field of education. The author concludes that information technologies arise on the quality of education in general, and in particular on teaching foreign languages. As an information system, the Internet offers a lot of information and resources for the effective construction of the educational process. The role of information and network technologies in the privileged quality of education of modern students is noted. It is noted in the article, that modern views on learning outcomes have led to the emergence of new technologies in teaching English and developing listening and speaking skills.
Keywords: information; developing; speaking; technologies